Factors conditioning the adoption rate of technified irrigation systems in Mexico - García-Salazar, José Alberto (2023)
Introduction. To know the factors that determine the rate of adoption of technician irrigation systems is important because of the water savings that could be obtained by increasing the number of units that use more efficient systems. Objective. To determine the factors that affect the rate of adoption of technician irrigation systems in Mexico. Materials and methods. A logit model was estimated where the dependent variable was the logit of the ratio of probabilities of using technician irrigation systems against other irrigation systems. The independent variables were: electricity price, water value, rainfall, temperature, number of over-exploited aquifers, farm size, utilization rate of production units that use sanitary measures, and educational level of agricultural producers. The estimate was made with data from Mexico’s 32 federative entities for 2019. Results. The results indicated that, if the electricity price and the water value increase by 10 %, the rate or probability of using modernized irrigation systems increases from 24.51 to 25.42 and 26.17 %, respectively. A 10 % decrease in rainfall would increase the probability of using modernized irrigation systems from 24.51 to 25.41 %, while with a 5 % increase in temperature, this probability would increase from 24.51 to 29.40 %. Conclusion. These results demonstrated the importance of economic and climatic conditions as factors that affect the use of technician irrigation systems, therefore, in saving water.